“Non-healing” claw horn lesions in dairy cows: Clinical, histopathological and molecular biological characterization of four cases - Alsaaod, Maher; Weber, Jim; Jensen, Tim; Brandt, Sabine; Gurtner, Corinne; Devaux, David; Studer, Eveline; Steiner, Adrian (Frontiers in Veterinary Science, 2022)
The increasing prevalence of bovine digital dermatitis (BDD) contributes to a higher occurrence of secondary infections of exposed corium with Treponema spp. in bovine claws. "Non-healing" claw horn lesions (NHL) clinically resemble BDD lesions. They are severe, cause chronic lameness, and may persist for several months. They poorly respond to standard treatments of BDD and represent a serious welfare issue. In this study, four cases of NHL were classified clinically either as BDD-associated axial horn fissures (BDD-HFA; n =3) or BDD-associated sole ulcer (BDD-SU; n=1). In all four cases, pronounced multifocal keratinolysis of the stratum corneum, ulceration, and severe chronic lymphoplasmacytic perivascular to interstitial dermatitis were observed. All lesional samples tested positive for Treponema spp., Fusobacterium (F.) necrophorum, and Porphyromonas (P.) levii by PCRs. BDD-HFA lesions contained Treponema pedis spp. as revealed by genetic identities of 93, 99, and 100%. Treponemes in the BDD-SU lesion were 94% homologous to Treponema phylotype PT3. Fluorescent in situ hybridization (FISH) revealed extensive epidermal infiltration by treponemes that made up > 90% of the total bacterial population in all four lesions. FISH also tested positive for P. levii and negative for F. necrophorum in all four cases, whilst only one BDD-HFA contained Dichelobacter nodosus. Our data point to BDD-associated treponemes and P. levii constituting potential etiological agents in the development of "non-healing" claw horn lesions in cattle.